Digital Age and Hospitality Human Resources Strategy of Development. The Case of the Japanese and Chinese Customers - Tavares de Carvalho, P. (Human Resources Development in a Digital Age (UFHRD 2024), 2025)
Tools of the digital age can be a useful tool to discuss and improve customer satisfaction, service quality and consequently the hotels’ strategy. Analyzing a hotel´s digital tool though the online travel agency: booking.com, the study uses a qualitative approach of content analysis, identifying the Japanese and Chinese customers ‘perceptions, satisfaction, and dissatisfaction about luxury hotels attributes. Findings of content reviews analysis (568 Japanese customers reviews and 968 Chinese customers reviews) reveal that Japanese and Chinese customers are pleased differently concerning hotel attributes and it falls into six dimensions: location, facilities, room, breakfast, staff-service, finance. This study has theoretical implications, confirming that these six dimensions are applied to Portugal but also to other countries, however this study also confirms that these dimensions are seen differently from Japanese and Chinese perspectives and can be grouped into the balanced scorecard dimensions. There are practical implications as Asian Customers are not all the same, hotels strategy should take in consideration the customer country of origin, this study contributes with highlights to develop Hotels Human Resources skills to meet Japanese and Chinese Hotel attributes´ expectations.